Oxidoreductase 2021
DOI: 10.5772/intechopen.95809
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal 5α-Reductase: A Therapeutic Target for Prostate Disorders

Abstract: Steroidal 5α-reductase is a system of NADPH dependent enzyme that catalyzes the irreversible conversion of Δ4–3-ketosteroid precursor (testosterone) to its corresponding 5α-reduced metabolite (dihydrotestosterone). Initial role of DHT was discovered through males pseudohermaphroditism, a genetic disorder with complete or partial 5α-reductase deficiency accompanied with features at critical juncture of fetal and postnatal development. However, excessive DHT production, has brought a revolution in revealing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The kinetic constant was based on the non-linear analysis and the Michaelis–Menten method gave a whole-cell K m value of 9.287 µM. Previous studies have shown a testosterone affinity, with K m value ranging from 1 to 5 µM in other cell lines, including dermal papilla, prostate cancer, and sebaceous glands 39 , 41 , 42 . Non-linear modeling of experimentally evaluated V max in the absence of inhibitors gave a V max value of 130.9.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetic constant was based on the non-linear analysis and the Michaelis–Menten method gave a whole-cell K m value of 9.287 µM. Previous studies have shown a testosterone affinity, with K m value ranging from 1 to 5 µM in other cell lines, including dermal papilla, prostate cancer, and sebaceous glands 39 , 41 , 42 . Non-linear modeling of experimentally evaluated V max in the absence of inhibitors gave a V max value of 130.9.…”
Section: Resultsmentioning
confidence: 99%